Respons Bibit Tebu (Sacharum officinarum L.) Terhadap Konsentrasi Zpt Dan Lama Penyimpanan Bahan Bibit - Gasta Putra Gunanda; Yatmin Yatmin; Krisnarini Krisnarini; Windu Mangiring (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2021)
This research was conducted at the STIPER Dharma Wacana Metro Experimental Garden, Rejomulyo Village, Metro Selatan Subdistrict, metro city from October 2020 to December 2020. This study used a complete randomized block design arranged in a factorial with three replications. The first factor is concentration (K) which consists of three levels, namely k1 = 2ml / l, k2 = 7ml / l, and k3 = 10.5ml / l. The second factor was the storage time for the seed material (L), which consisted of three levels of l1 = 3 days, 12 = 5 days, and 13 = 7 days. The results showed that, the concentration of PGR had no significant effect on the growth of sugarcane seeds except for the percentage of shoot growth, the best PGR concentration was found at 2 ml / l. The storage time for seed material had no significant effect on the growth of sugarcane seeds. There was no interaction between the concentration of PGR and the storage time for sugarcane seedlings on the growth of sugarcane seeds.